Pengaruh Kompetensi, Lingkungan Kerja Fisik Dan Motivasi Terhadap Kepuasan Kerja Karyawan Pada PT. Semarang Indah Era Modern Semarang - Ravit Effendi; Wachid Fuady R (Jurnal Ekonomi Manajemen Akuntansi, 2021)
Managing human resources optimally, in this case employees in an organization, both non-governmental organizations and governmental organizations, is very important in conditions with an increasingly high level of competition. Employees needed at this time are those who have the attitude to carry out their duties and responsibilities properly, so that the goals to be achieved can be realized. Various problems that are currently being faced require companies/organizations to find solutions that are fast, precise, and accurate, especially problems related to human resources in companies/organizations. In this condition, it cannot be denied that labor or employees are the lifeblood and the most important element that is needed by the company/organization, without employees it is difficult to achieve the desired goals. Sutrisno (2012) that the biggest real threat to economic stability is a workforce that is not ready to face the challenges and changes that are happening around it. Thus, efforts are needed to be able to create and form employees who have a loyal attitude towards work, have creativity, are able to demonstrate work innovation, have forward orientation, and have the ability to think critically.